Lythria (Microlythria subgen. nov.) venustata Staudinger, 1882 (Lepidoptera: Geometridae): distribution and description of the female, with a brief review of the genus - Makhov, I.a.; Gorbunov, P.yu.; Lukhtanov, V.a. (Zootaxa, 2024)
The article provides new localities for the little-known species Lythria venustata Staudinger, 1882; a map with all currently known locations is presented. A new subgenus, Microlythria subgen. nov., within Lythria Hübner is proposed for L. venustata. A morphological description of L. venustata female and illustration of its genital structure are given for the first time; some corrections in the description of the male genitalia are made. Both male and female genitalia of all other species of the genus are also shown, and a comparison of L. venustata with its congeners is made. Colour plates depicting males and females of all species of the genus Lythria are provided. The systematic position of the genus in the family Geometridae, and the implication of the features of L. venustata female genitalia for tribal association within the Sterrhinae are discussed. Identification keys (based on external morphology and genital structure) to Lythria species are given.